Neuropsychological performance in patients with substance use disorder with and without mood disorders - Höijer Irma; Ilonen Tuula; Löyttyniemi Eliisa; Salokangas Raimo KR (TAYLOR & FRANCIS LTD, 2025)
Background: Mood disorders commonly co-occur in patients with substance use disorders (SUD). This combination may increase the risk of pathological effects and impair cognitive functioning.
Aim: The aim of the study was to examine the effects of mood and substance use disorders on specific neuropsychological measures.
Methods: The participants comprised 164 hospitalised patients, 88 with (SUD + MD) and 76 (SUD-MD) without mood disorders, ranging in age from 19 to 65 years. Their diagnostic assessment was based on a psychiatric interview (ICD-10). Neuropsychological tests were carried out after a minimum of one month of abstinence.
Results: Processing speed (p = 0.029), and perceptual reasoning (p = 0.039) were more impaired in the SUD + MD group than in the SUD-MD group. An Analysis of covariance (ANCOVA) controlled for age, education level, learning difficulties and polysubstance use revealed that the groups were most powerfully separated by the Digit Symbol test and the Block Design test.
Conclusions: Patients with substance abuse and mood disorders seem to have more deficits in speed processing and perceptual reasoning than substance abuse patients without mood disorders. These processing speed difficulties and perceptual problems may impact prognosis and treatment. The Digit Symbol test and the Block Design test are a fast and sensitive ways to examine treatment effectiveness and monitor treatment progress.